PERAN ORANG TUA MILENIAL DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR DI ERA DIGITAL - hifayatulloh, Ahmad aris; Khoirudin, Muhammad Abdul Rozaq (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Ngawi, 2024)
ABSTRACT : Parents' involvement in their children's education is vital to their general well-being and academic achievement. Parents who play an active role in their children's education can nurture a love of learning, encourage effective learning techniques, and provide the support and tools their children need to succeed. Besides, healthy parent-child interactions can enhance communication and strengthen the sense of support and encouragement that exists in the home. This study explores the influence of the participation of millennial parents in children's education. Using literature-based qualitative research methods, the study analyzes various sources to understand how parental involvement can affect children's educational outcomes. The findings suggest that the active involvement of millennial parents, such as attending parent-teacher conferences, helping with homework, and regulating the use oftechnology, has a positive impact on children's digital literacy and academic achievement. Engaged parents can boost their child's learning motivation, confidence, and critical thinking skills. However, excessive involvement can create stress and anxiety. The study emphasizes the importance of collaboration between parents and teachers to create a supportive and productive educational environment, as well as recommendations to increase parents' involvement in children's education.